Increasing Regional Tax Revenue Through The Implementation of a Motor Vehicle Payment System - Andi Rustam; Andi Arifwangsa Adiningrat; Risfayana Hasan (Jurnal Riset Perpajakan: Amnesty, 2023)
This study aims to evaluate the increase in local tax revenue through the implementation of a motorised vehicle tax payment system. The object of research is "Implementation of the Motor Vehicle Tax Payment System at the Takalar Regency Samsat Office". The research method used is an applied qualitative approach. Data collection techniques involved interviews, documentation, and observation. The results of this study indicate that the motor vehicle tax payment system through the innovation of stationary Samsat and mobile Samsat at the Takalar Regency Samsat Office has been realised as expected. This system provides convenience for taxpayers in paying motor vehicle taxes and increases taxpayer compliance in fulfilling their tax obligations. In addition, the implementation of this system has also accelerated the process of collecting and managing local tax revenues, which significantly has a positive impact on local revenues. The availability of Mobile Samsat has also enabled better accessibility for taxpayers in remote areas. This research makes an important contribution to the understanding of the effectiveness of the motor vehicle tax payment system in increasing local revenue as well as providing recommendations for further improvement.